Heterogeneity of phenotypic manifestations of cystic fibrosis in children and predictors of the disease severity - K. V. Skriabina; S. I. Ilchenko; A. O. Fialkovska (Zaporožskij Medicinskij Žurnal)
The aim of the study was to investigate the heterogeneity of phenotypic manifestations of cystic fibrosis (CF) in children depending on the CFTR gene mutation and to determine predictors of the disease severity for the personalization of treatment and prevention of complications.